Perilaku Belanja Webrooming Intention Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Dharma Andalas - Mohammad Abdilla; Idwar Idwar (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
The purpose of this study was to determine the effect of perceived usefullness of online search, perceived ease of online search, need for touch, sales staff assistance, socialization on the webrooming intention of FEB Dharma Andalas University students. The research sample consisted of 292 people using the Slovin formula. Primary data was collected using a non-probability sampling technique using a Likert scale questionnaire. All the results of the instrument test and the classical assumption test complied in order to obtain the equation Y = 0.028 + 0.095X1 - 0.291X2 + 0.406X3 + 0.486X4 + 0.156X5 + e. The results of partial hypothesis testing show perceived usefullness of online search, perceived easy of online search, need for touch, sales staff assistance have a significant positive effect on webrooming intention of FEB students at Dharma Andalas University except socialization has a significant negative effect on webrooming intention. Correlation of perceived usefullness of online search, perceived ease of online search, need for touch, sales staff assistance, socialization with high webrooming intention 0.915. Perceived usefullness of online search, perceived ease of online search, need for touch, sales staff assistance, socialization is able to explain the webrooming intention of undergraduate students of Management FEB Dharma Andalas University by 0.835 while the remaining 0.165 is explained by other variables not included in the research model. ABSTRAK Tujuan penelitian ini adalah mengetahui pengaruh perceived usefullness of online search, perceived easy of online search, need for touch, sales staff assistance, socialization, terhadap webrooming intention mahasiswa FEB Universitas Dharma Andalas. Sampel penelitian terdiri dari 292 orang menggunakan rumus Slovin. Data primer dikumpulkan dengan teknik non probability sampling menggunakan angket skala Likert. Semua hasil uji instrumen dan uji asumsi klasik memenuhi sehingga didapat persamaan Y = 0,028 + 0,095X1 - 0.291X2 + 0.406X3 + 0,486X4 + 0,156X5 + e. Hasil pengujian hipotesis secara parsial menunjukkan perceived usefullness of online search, perceived easy of online search, need for touch, sales staff assistance berpengaruh positif signifikan terhadap webrooming intention mahasiswa FEB Universitas Dharma Andalas kecuali socialization berpengaruh negatif signifikan terhadap webrooming intention. Korelasi perceived usefullness of online search, perceived easy of online search, need for touch, sales staff assistance, socialization dengan webrooming intention tinggi 0,915. Perceived usefullness of online search, perceived easy of online search, need for touch, sales staff assistance, socialization mampu menjelaskan webrooming intention mahasiswa prodi S1 Manajemen FEB Universitas Dharma Andalas sebesar 0,835 sedangkan sisanya 0,165 dijelaskan oleh variabel lain yang tidak termasuk ke dalam model penelitian